Sistematik Review Aktivitas Buah Pare (Momordica charantia L.) Terhadap Target Molekuler Antidiabetes - Mega Ayu Kusniawati (Jurnal Farmasi Indonesia, 2021)
Diabetes mellitus (DM) is a chronic disease that occurs either when the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it produces. The purpose activity of bitter melon fruit against molecular targets antidiabetic in literatre review. Analysis and systematic web search reviews were carried out on the research literature related to bitter melon which is used for DPP4, PTP1B, α-glucosidase, and increasing GLUT4 levels. The data were collected from several journals with inclusion criteria. The data were extracted and synthesized. The charantin, cucurbitacin, dan momordicoside D compound from bitter melon fruit has activating the TGR5 and GLP1 receptor simultaneously inhibiting DPP4. The cucurbitane 25-O-methylkaraviagein D the of bitter melon fruit has inhibitory activity against the PTP1B enzyme which is associated with the presence of –OH, The 3β,7β,25-trihydroxycucurbita-5,23(E)-dien-19-al, charantal, charantoside XI, dan 25ξ- isopropenylchole-5, 6-ene-3-O- D-glukopiranosida α-glucosidase predicted to have inhibitory activity of binding to the active side of the protein. The vicine, polypeptide-p, 5-,19-epoxy-3-, 25-dihydroxycucurbita-6,23 (E) -diene dan 3-7-,25-trihydroxycucurbita-5,23 (E)-dien-19-al can increase the amount of GLUT4 on the cell surface.